LEONAS JOVAIŠA CONTRIBUTIONS TO THE PRACTICE&NBSP;AND RESEARCH OF VOCATIONAL GUIDANCE - Pociūtė, Birutė (Acta Paedagogica Vilnensia, 2010)
This article celebrates the 90th anniversary of Professor Leonas Jovaiša and the 50th anniversary of the first publications in the field of vocational guidance. Career development and career choice theory have a rich history, but theoretical findings of career development in the Lithuania are very fragmentary. Professor Leonas Jovai a is one of scientists who presents a complete model of vocational guidance system in the Lithuania. The aim of the article is to present and describe the main facts about vocational guidance system of sixties of twentieth century in Leonas Jovai a research findings. The article describes L. Jovaiša’s contribution to creating the vocational guidance system in Lithuania: macro, mezo and micro levels of guidance system. Much attention is focused on developmental nature of career guidance and career counseling. Several aspects of career counseling is discussed: the integrated nature of career counseling, the multifaceted set of activities to help people make vocational choice, education based career guidance, the stages of career counseling. The article presents some comments on concept career as calling.